Neural network-assisted eco-architectural designs: Conceptualizing sustainable construction solutions - Zatsepina Aleksandra; Mikhaylovskaya Liudmila; Shindina Polina (E3S Web of Conferences)
Nowadays, neural networks are increasingly being used to generate sketchy architectural solutions. In this article, two projects that won the architectural competition are used as examples to demonstrate how to use the MidJorney neural network. Examples are given for generating text from the source image, generating images based on text queries and making corrections, combining images, images, and text, and altering an image fragment. A roadmap has been drawn up—an algorithm for using the MidJorney neural network to work on an architectural concept.